2014
DOI: 10.4161/auto.28679
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy promotes resistance to photodynamic therapy-induced apoptosis selectively in colorectal cancer stem-like cells

Abstract: Recent studies have indicated that cancer stem-like cells (CSCs) exhibit a high resistance to current therapeutic strategies, including photodynamic therapy (PDT), leading to the recurrence and progression of colorectal cancer (CRC). In cancer, autophagy acts as both a tumor suppressor and a tumor promoter. However, the role of autophagy in the resistance of CSCs to PDT has not been reported. In this study, CSCs were isolated from colorectal cancer cells using PROM1/CD133 (prominin 1) expression, which is a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
137
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(144 citation statements)
references
References 64 publications
(59 reference statements)
4
137
0
3
Order By: Relevance
“…Downregulation of HSP70 increased PDT sensitivity and mediated PDT-induced apoptosis. Wei et al reported that autophagy is associated with PDT resistance in colorectal cancer stem-like cells (30). Autophagy and apoptosis may be triggered by common signals, resulting in combined autophagy and apoptosis.…”
Section: Hsp70 Plays a Fundamental Role In Protecting Cells Against Pdtmentioning
confidence: 99%
“…Downregulation of HSP70 increased PDT sensitivity and mediated PDT-induced apoptosis. Wei et al reported that autophagy is associated with PDT resistance in colorectal cancer stem-like cells (30). Autophagy and apoptosis may be triggered by common signals, resulting in combined autophagy and apoptosis.…”
Section: Hsp70 Plays a Fundamental Role In Protecting Cells Against Pdtmentioning
confidence: 99%
“…Autophagy activation was observed in colon cancer stem cells by analysis of the expression of the intestinespecific transcription factor Cdx1, which plays a crucial role in chemoresistance to paclitaxel [106] . Similarly, autophagy increased resistance to photodynamic therapyinduced apoptosis in CRC stemlike cells [139] . However, this report did not address whether the protective autophagy that was induced in cancer stem cells was due to a drug mediated response to stress or to the inherent ability of cancer stem cells to maintain a high threshold for autophagy.…”
Section: Autophagy Drugs In Crcmentioning
confidence: 99%
“…It has been reported that autophagy increases the resistance of colorectal cancer stem-like cells to photodynamic therapy-induced apoptosis (1,27,28). Similarly, cisplatin-activated autophagy, involving the activation of ATG7, has been indicated to increase liver cancer cell resistance to cisplatin (29).…”
Section: Discussionmentioning
confidence: 99%